GOOGLE FIBER - Singh, Sanjana; Bhardwaj, Surbhi; Mudgil, Shivansh (IJRDO -Journal of Computer Science Engineering, 2015)
Google Fiber is Google's fiber-to-the-premises service in the United States,providing broadband internet and television to a small and slowly increasing number oflocations.[1] The service was first introduced to Kansas City, Kansas,[2] and is being rolled outto Kansas City, Missouri, with plans for expansion to several other Kansas City area suburbs,as well as Austin, Texas, and Provo, Utah. In February 2014, Google announced they hadchosen another 34 cities in 9 metro areas as candidates for future expansion.[3] In January 2015,Google selected Atlanta, Charlotte, Raleigh, Durham, and Nashville as the next markets thatwill receive Google Fiber deployments.Google Fiber has been around for a little while, but the concept is still fairly new to manybecause the service is not yet offered nationwide. Google Fiber is an advanced fiber opticnetwork designed to deliver Internet speeds up to 100 times faster than standard broadbandconnections. The Fiber network also offers: HD television programming with less compression (meaning clearer pictures) DVR (digital video recording) with up to eight simultaneous programs and 2 TB ofstorage Apps for more control over television and InternetThe process promises to be long, however, because Google needs to erect the necessaryinfrastructure in all cities to which it will deliver Fiber services. Fiber is currently available onjust a few U.S. cities, but Google has plans to take the service much further